2006
DOI: 10.1038/nn1808
|View full text |Cite
|
Sign up to set email alerts
|

SYD-2 Liprin-α organizes presynaptic active zone formation through ELKS

Abstract: A central event in synapse development is formation of the presynaptic active zone in response to positional cues. Three active zone proteins, RIM, ELKS (also known as ERC or CAST) and Liprin-alpha, bind each other and are implicated in linking active zone formation to synaptic vesicle release. Loss of function in Caenorhabditis elegans syd-2 Liprin-alpha alters the size of presynaptic specializations and disrupts synaptic vesicle accumulation. Here we report that a missense mutation in the coiled-coil domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
289
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(312 citation statements)
references
References 38 publications
23
289
0
Order By: Relevance
“…1a) and Liprin-α (Syd-2) promote presynaptic assembly 5,[15][16][17][18] . When we expressed Nlg1∆Cyto in a Liprin-α mutant background, NMJ terminals still showed severe under-growth compared to those in the Liprin-α mutant background alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) and Liprin-α (Syd-2) promote presynaptic assembly 5,[15][16][17][18] . When we expressed Nlg1∆Cyto in a Liprin-α mutant background, NMJ terminals still showed severe under-growth compared to those in the Liprin-α mutant background alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, identifying proteins coupling Nrx-Nlg to the assembly process itself and defining where in the sequence of events Nrx-Nlg acts is critical for a deeper understanding of synapse formation and remodeling. Independent work in model organisms has identified and characterized proteins guiding active zone assembly, with Syd-1 proteins functioning upstream of Syd-2 (Liprin-α) 5,15,16 . In vivo imaging demonstrated that both Syd-1 and Liprin-α accumulate very early during synapse assembly (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the molecules involved in early formation of active zones, such as liprins and CAST/ELKS/ERC proteins, also contribute to or correlate with changes in active zone size in mature synapses (Zhen and Jin, 1999;Kaufmann et al, 2002, p 2;Olsen et al, 2005;Dai et al, 2006;Astigarraga et al, 2010;Lazarevic et al, 2011). Active zone size can change over different timescales from minutes (Matz et al, 2010) to hours (SpiwoksBecker et al, 2004;Hull et al, 2006) to days (Lazarevic et al, 2011), accompanying changes of synaptic activity and the circadian cycle.…”
Section: Reduced Active Zone Size But Preserved Molecular Synapse Anamentioning
confidence: 99%
“…We hypothesize that CAST, as a molecular scaffold with multiple binding sites for other cytomatrix proteins, contributes to the proper lateral assembly of the ribbon and the arciform density to establish and/or stabilize a full-length active zone. Other candidates mediating stabilization might be liprin-␣s (Dai et al, 2006) and in particular liprin-␣4, because it shows an overlapping expression pattern with other CAZ proteins at rod photoreceptor synapses. It seems, however, not to be confined to the active zone (Zürner et al, 2011).…”
Section: Reduced Active Zone Size But Preserved Molecular Synapse Anamentioning
confidence: 99%
“…Morphological elucidation of the active zone suggests that a protein scaffold organizes the active zones and links it physically to presynaptic vesicles [6] . To date, mainly three active zone proteins have been identified in Caenorhabditis elegans as the synaptic scaffolds: UNC-10/ RIMs are putative Rab3A-effectors in regulating synaptic vesicle exocytosis and neurotransmitter release [7] , Unc-13/ Munc-13s are required for priming synaptic vesicles for exocytosis and synaptic transmission [8] , and α-liprins/SYD-2 bind to and recruit tyrosine phosphatases (receptor type) to defined areas for active zones development and normal active zone function [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%